MESJID WANITA DI SUNGAI LIMAU KABUPATEN PADANG PARIAMAN (Kajian Sejarah Sosial) - Siti Aisyah; Asril Asril (Turast: Jurnal Penelitian dan Pengabdian, 2015)
This paper is intended to reveal the existence of a mosque in Sungai Limau, Padang Pariaman, the so-called"female mosque". This naming seems unusual, because the trend of naming mosques usually uses Arabic words.Not just naming, but the mosque is actually being used by women, from its founders, managers, until thecongregation. On Friday, the mosque does not conduct Friday prayers, but the congregated noon prayer forwomen. recently, this mosque holds Friday prayers. Above this reason, it is important to do further study on themosque. By using historical-sociological approaches, this study reveals that female mosque originated from ahouse for gathering elderly women to chatt, then it turned into the mosque where they pray, study Islam, stay,and do business. This mosque later changed its name to the Female Mosque to deal with the help of an Arabgovernment at the time. Several years after the change of the name of the Female Mosque, there was a transferof function: the mosque is no longer for women only, but also to the public (men and women)